Implementation of Social Customer Relationship Management as a Sustainability Strategy of Banyumas MSMEs in the Covid-19 Pandemic - Akbar Pahlevi; Andhi Johan S (Budapest International Research and Critics University, 2022)
The purpose of the study is to analyze the implementation of SCRM as a business continuity strategy during the Covid-19 pandemic by taking a case study on MSMEs in Banyumas Regency. This study uses a descriptive approach. The data collection technique used in this study was library observation as a technique for collecting data (Hardilawati, 2020). For data collection and analysis, the NVivo Release 12.00 plus for Windows application with a database of links or URLs is used. The result of this study are MSMEs in Banyumas lack the resilience and flexibility in dealing with this pandemic due to several things, such as the level of low digitization, difficulties in accessing technology, and lack of understanding of strategies to survive in business. MSMEs are required to be able to adapt to existing business developments because businesses that can survive are businesses that are responsive to the times.